ANALISIS PENERAPAN AKUNTANSI ZAKAT, INFAQ/SEDEKAH PADA BADAN AMIL ZAKAT NASIONAL KOTA KOTAMOBAGU - Rahmadani, Fitri; Karamoy, Herman; Afandi, Dhullo (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
The application of accounting zakat in management of zakat, infaq/charity is very recommended that creation of tranparent financial reporting and accountability. While the main principle of zakat management still putting honesty and the trust of these factors make less disbelief muzakki to zakat management. The purpose of this study was to determine the application of accounting zakat based on SFAS No. 109 on Baznas Kotamobagu City. While the purpose of the application of SFAS No. 109 which is to regulate the recognition, measurement, presentation and disclosure of transactions zakat, infaq/charity to the other amil zakat institutions nationwide. This type of research is a qualitative study using descriptive methods. From the result of this research in the recognition, measurement and disclosure Baznas Kotamobagu City has not fully implemented in accordance with SFAS No. 109, for presentation and financial reporting Baznas Kotamobagu City only reports the reception and distribution of zakat, have yet to implement component based on SFAS No. 109. In this case you should Amil Zakat Kotamobagu City soon prepare a report based on SFAS No. 109 so that the main principle of amil zakat board Kotamobagu City not only honesty and trustworthy but also accountability and transparency.Keywords : Accounting Zakat, Infaq /charity, Financial Statements